Neuroregression as an initial manifestation in a toddler with acquired pernicious anaemia. (17th December 2015) - Yoganathan, Sangeetha; Thomas, Maya Mary; Mathai, Sarah; Ghosh, Urmi
Abstract : The aetiology spectrum for neuroregression in infants and toddlers is diverse. Vitamin B12 deficiency-mediated neuroregression is less commonly considered as a differential. Prevalence of pernicious anaemia in the general population is 0.1% and is extremely rare in children. We describe a 35-month-old toddler with neuroregression, seizures, coarse tremors, bleating cry and neuropathy. His clinical symptomatology mimicked grey matter degenerative illness and infantile tremor syndrome, a nutritional deficiency-mediated movement disorder. His vitamin B12 level was low and serum homocysteine level was elevated. Haematological manifestations were not overt and anti-intrinsic factor antibody was positive. With parenteral vitamin B12 therapy, there was a dramatic response with clinical and laboratory translation. This report emphasises the need for a high index of suspicion and screening for markers of vitamin B12 deficiency in all children with unexplained acute or subacute neuroregression, seizures and movement disorders as it is potentially reversible.